Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.2 - Negative Exponents and Scientific Notation - Exercise Set: 122

Answer

$9a^{6}$

Work Step by Step

$(2a^{3})^{3}a^{-3}+a^{11}a^{-5}=2^{3}a^{3\times3}a^{-3}+a^{11}a^{-5}=8a^{9}a^{-3}+a^{11}a^{-5}=8a^{9+(-3)}+a^{11+(-5)}=8a^{6}+a^{6}=9a^{6}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.